Tests of positive ion beams from a microwave ion source for AMS - Schneider, R. J.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C.; Kern, W. G. E.; Kim, S. W. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2000)
A test facility has been constructed to evaluate high-current positive ion beams from small gaseous samples for AMS applications. The major components include a compact permanent magnet microwave ion source built at the AECL Chalk River Laboratory and now on loan from the University of Toronto, and a double-focusing spectrometer magnet on loan from Argonne National Laboratory. Samples are introduced by means of a silica capillary injection system. Loop injection into a carrier gas provides a stable feed for the microwave driven plasma. The magnetic analysis system is utilized to isolate carbon ions derived from CO? samples from other products of the plasma discharge, including argon ions of the carrier gas. With a smaller discharge chamber, we hope to exceed a conversion efficiency of 14% for carbon ions produced per atom, which we reported at AMS-7. The next step will be to construct an efficient charge-exchange cell, to produce negative ions for injection into the WHOI recombinator injector. (C) 2000 Elsevier Science B.V. All rights reserved.
372jrTimes Cited:16Cited References Count:4